Eye drop neurology. Issue 3 (11th February 2014) - Bennetto, Luke; Guly, Catherine; Ormerod, Ian; Plant, Gordon T
Abstract : Eye drops can help to diagnose and prevent complications of neurological disorders. Guttae ophthalmicae (eye drops) are generally safe because the drugs rarely achieve significant systemic concentrations, although there are rare exceptions. This article covers contemporary pharmacological pupil testing; how to dilate a pupil safely; common reasons why pupils do not respond to drops; and corneal lubrication to prevent complications of weak eye closure.